Lessons from two high CO2 worlds – future oceans and intensive aquaculture. (20th October 2016) - Ellis, Robert P.; Urbina, Mauricio A.; Wilson, Rod W.
Abstract: Exponentially rising CO2 (currently 400 μatm) is driving climate change and causing acidification of both marine and freshwater environments. Physiologists have long known that CO2 directly affects acid–base and ion regulation, respiratory function and aerobic performance in aquatic animals. More recently, many studies have demonstrated that elevated CO2 projected for end of this century (e.g. 800–1000 μatm) can also impact physiology, and have substantial effects on behaviours linked to sensory stimuli (smell, hearing and vision) both having negative implications for fitness and survival. In contrast, the aquaculture industry was farming aquatic animals at CO2 levels that far exceed end‐of‐century climate change projections (sometimes >10 000 μatm) long before the term 'ocean acidification' was coined, with limited detrimental effects reported. It is therefore vital to understand the reasons behind this apparent discrepancy. Potential explanations include 1) the use of 'control' CO2 levels in aquaculture studies that go beyond 2100 projections in an ocean acidification context; 2) the relatively benign environment in aquaculture (abundant food, disease protection, absence of predators) compared to the wild; 3) aquaculture species having been chosen due to their natural tolerance to the intensive conditions, including CO2 levels; or 4) the breeding of species within intensive aquaculture having further selected traits that confer tolerance to elevated CO2 . We highlight this issue and outline the insights that climate change and aquaculture science can offer for both marine and freshwater settings. Integrating these two fields will stimulate discussion on the direction of future cross‐disciplinary research. In doing so, this article aimed to optimize future research efforts and elucidate effective mitigation strategies for managing the negative impacts of elevated CO2 on future aquatic ecosystems and the sustainability of fish and shellfish aquaculture.